2020
DOI: 10.1101/2020.02.12.945576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aberrant pathogenic GM-CSF+T cells and inflammatory CD14+CD16+monocytes in severe pulmonary syndrome patients of a new coronavirus

Abstract: Pathogenic human coronavirus infections, such as severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV), cause high morbidity and mortality 1,2. Recently, a severe pneumonia-associated respiratory syndrome caused by a new coronavirus was reported at December 2019 (2019-nCoV) in the city Wuhan, Hubei province, China3–5, which was also named as pneumonia-associated respiratory syndrome (PARS)6. Up to 9th of February 2020, at least 37, 251 cases have been reported wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
301
1
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(336 citation statements)
references
References 29 publications
14
301
1
20
Order By: Relevance
“…These findings supported a hypothesis that rapid production of IL-6 might be a possible mechanism leading to the deleterious clinical manifestations in viral pathogenesis [24]. Recently published researches on the clinical characteristics of severe patients with SARS-CoV-2 infection showed that IL-6 was significantly elevated especially in those ICU patients, which caused excessive activated immune response [25,26,27,28,29]. The pathological role of IL-6 in SARS-CoV-2 infection indicated that IL-6 blockade may provide a feasible therapy for the treatment of COVID-19.…”
Section: Cvl218 Inhibits Il-6 Production In Pbmcs Induced By Cpg-odnsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings supported a hypothesis that rapid production of IL-6 might be a possible mechanism leading to the deleterious clinical manifestations in viral pathogenesis [24]. Recently published researches on the clinical characteristics of severe patients with SARS-CoV-2 infection showed that IL-6 was significantly elevated especially in those ICU patients, which caused excessive activated immune response [25,26,27,28,29]. The pathological role of IL-6 in SARS-CoV-2 infection indicated that IL-6 blockade may provide a feasible therapy for the treatment of COVID-19.…”
Section: Cvl218 Inhibits Il-6 Production In Pbmcs Induced By Cpg-odnsupporting
confidence: 79%
“…Notably, current pathological studies have shown that the severe patients infected by SARS-CoV-2 generally have higher plasma levels of IL-2, IL-6, IL-10, TNFα, IFN-γ [25,27,28,29], implying a high risk of the inflammatory-associated cytokine storm after viral infection. In addition, reduction and functional exhaustion of T cells have also been observed in COVID-19 patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Zhou and colleagues recently reported on the presence of a significantly higher percentage of CD14 + CD16 + inflammatory monocytes in the peripheral blood of COVID-19 patients compared to normal healthy controls. 17,18 They also reported that the percentage of CD14 + CD16 + monocytes was much higher in severe pulmonary syndrome patients from ICU. They also showed that these monocytes had the capability of secreting GM-CSF and similar to our findings could also secrete IL-6, which was higher in ICU patients, in association with cytokine storm.…”
Section: In a Review Of The Causes And Consequences Of Cytokine Stormmentioning
confidence: 94%
“…Current research suggests that cytokine release syndrome (CRS) caused by immune imbalance following SARS-CoV-2 infection may be an important cause of diffuse microvascular injury. Researchers analyzed 30 immunological parameters in the blood of 33 COVID-19 patients and speculated that the mechanism of inflammatory damage may be T cell activation following SARS-CoV-2 infection and production of a large amount of granulocyte-macrophage colony-stimulating factor and IL-6, which induces a cascade of inflammatory factors (11). IL-6 can cause coagulopathies through many pathways.…”
Section: Comparison Of Coagulation Function Parameters Between Thementioning
confidence: 99%